Bridging Academic Stress and Burnout: Procrastination as a Mediator and Implications for Education Policy - Brandon N. Obenza; Marlou Jay G. Fordan; Jianna Mae S. Tripole; Frankie Dawn Erica C. Cantor; Archer James G. Parantar; Alexis Joseph M. Florenosos; Aice Jean B. Ando; Apple Mae C. Reyes; Gideon S. Sumayo (Journal of Social Knowledge Education (JSKE), 2025)
Purpose of the study: This study aimed to examine the mediating role of academic procrastination in the relationship between academic stress and burnout among college students in Regions XI and XII, Philippines. Methodology: The study employed a quantitative, non-experimental correlational design. Data were collected through an online survey consisting of 64 items rated on a 5-point Likert scale. A sample of 250 college students was selected using stratified random sampling, and data were analyzed using SmartPLS 4.0 and bootstrapping with 5,000 resamples. Main Findings: The results showed that academic stress significantly predicts burnout (β = 0.394, p < 0.001), while procrastination mediates this relationship by amplifying stress and increasing emotional exhaustion (β = 0.411, p < 0.001). These findings highlight stress as a critical factor in driving burnout and demonstrate the importance of addressing procrastination to improve student well-being. Novelty/Originality of this study: This study advances knowledge by exploring the mediating role of procrastination in the stress-burnout relationship, which has been underexplored in the literature. It highlights practical implications for community-based education policies and strategies to enhance student resilience and mitigate burnout in academic settings.